2018
DOI: 10.1158/1538-7445.am2018-110
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 110: PPARγ loss increases the metastatic potential of HER2+ breast cancer

Abstract: Breast tumors that overexpress human epidermal growth factor receptor 2 (HER2+) grow and spread faster than HER2-negative tumors, resulting in poor patient prognosis. Peroxisome proliferator-activated receptor (PPAR)γ is a nuclear transcription factor that controls the expression of genes essential for normal metabolism of fats and sugars in the body. Our laboratory previously showed that PPARγ expression suppresses environmental carcinogen DMBA-mediated breast tumor progression in vivo, and PPARγ-activating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…PPARG constitutes heterodimer with retinoid X receptor and thus conducts transcription of multiple genes, which mainly regulates adipocyte differentiation and is related to cancer, inflammation, and atherosclerosis. 84 In BC, researches indicated that PPARG inhibited tumor progression 85 , 86 , 87 as a promising antineoplastic agent in the clinic. 88 …”
Section: Discussionmentioning
confidence: 99%
“…PPARG constitutes heterodimer with retinoid X receptor and thus conducts transcription of multiple genes, which mainly regulates adipocyte differentiation and is related to cancer, inflammation, and atherosclerosis. 84 In BC, researches indicated that PPARG inhibited tumor progression 85 , 86 , 87 as a promising antineoplastic agent in the clinic. 88 …”
Section: Discussionmentioning
confidence: 99%